Development of cyclodextrin stationary phases via 'click' chemistry for chiral capillary electrochromatography and high performance liquid chromatography - Wang, Yong (2011)
Due to increasing demand for enantiomerically pure (enantiopure) compounds, especially those of pharmaceutical importance, the development of stereoselective separation technologies has been attracting great attention during last decades. Direct enantioseparation by chiral stationary phases (CSPs) using chromatographic methods remains as the most important technique for chiral analysis as well as for preparative-scale chromatography. The development of novel stable and powerful CSPs is therefore important. High performance liquid chromatography (HPLC) is the most widely used separation technique and will continue to play an important role due to its maturity and easy operation. More recently, capillary electrochromatography (CEC), a new hybrid technology based on HPLC and capillary electrophoresis (CE), has been demonstrated to be a powerful alternative to chromatographic methods with several advantages over HPLC and CE. There are several interrelated objectives in this dissertation project. Firstly, a new synthetic methodology was developed for the preparation of cyclodextrin (CD) based CSPs via copper (I) catalytic 1,3-dipolar cycloaddition reaction (“click” chemistry). The second objective has been to fabricate chiral capillary columns with selected CD CSPs for CEC enantioseparation and investigate the effects of CEC parameters on the separation. Finally, the enantiorecognition abilities of the obtained CD CSPs were fully investigated for enantioseparation of a large variety of racemic compounds in reversed phase HPLC.